Aspectos ambientais e valoração econômica do Morro do Careca, Natal-RN - Pedroza, Francisco de Assis (2013)
The urbanization process in the recent decades has generated problems of considerable severity related to the physical and environmental use and occupation of cities. Economic growth and environmental preservation are often considered antagonistic goals. The question is no longer to grow or not to grow, but how to grow. The interactions between humans and the environment are accentuated in a strictly utilitarian perspective, which aim especially at the economic exploitation. The objective of this study is to investigate the economic valuation of the environmental resource called "Morro do Careca", located at the southern end of Ponta Negra beach in Natal in Rio Grande do Norte - Brazil. In this paper, it was sought to highlight the importance of assigning a monetary value to natural resources. The most used concept in the valuation of natural assets is the willingness to pay and refers to the maximum willingness to pay a person shows when using an environmental resource, considering one s budget, his preference and altruism. In the object under study, it was analyzed the direct use value (DUV) or its no use, since it was analyzed the benefit in the form of visitation of the Morro do Careca or its no visitation. Questionnaires were administered to the students of the Tourism school and Mechanics school at the Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN). It was used the Contingent Valuation Method (CVM) to capture the variable willingness to pay for the Morro. It was identified that the average age of respondents is of 22 year-olds. Most are willing to pay for the maintenance of the Morro, whose average value is $ 45.00, constituted primarily of tourism students; those who are not willing to contribute claim living under high taxation values already. In short, it was revealed that people are willing to contribute with $ 8.00 for the maintenance of the Morro do Careca, which leads to the inference that they value this spot of the city and thus recognize its importance to the environment and the city. It is observed that people enjoy directly or indirectly from the preservation of the Morro, through walking, hiking and through the economic value that aggregates to everything in its surroundings. Finally, we conducted a regression analysis through which we investigated the explaining variables gender, age and family income, simultaneously, about the willingness to pay. In the adjustment model, only in the tourism class there was significant difference (5%) between the variable willingness to pay for the maintenance of Morro do Careca and the variable gender.